STUDY ON ENSURING DATA STORAGE SECURITY SYSTEM IN CLOUD COMPUTING SERVICE (International Journal of Engineering and Computer Science, 2015)
Cloud Computing has been envisioned as the next-generation architecture of IT Enterprise. It moves the application software and databases to the centralized large data centers, where the management of the data and services may not be fully trust worthy. This unique paradigm brings about many new security challenges, which have not been well understood. This paper proposed a problem of ensuring the integrity of data storage in Cloud Computing. In particular, consider the task of allowing a third party auditor (TPA), on behalf of the cloud client, to verify the integrity of the dynamic data stored in the cloud. The introduction of TPA eliminates the involvement of the client through the auditing of whether his data stored in the cloud are indeed intact, which can be important in achieving economies of scale for Cloud Computing. While prior works on ensuring remote data integrity often lacks the support of either public auditability or dynamic data operations, first identify the difficulties and potential security problems of direct extensions with fully dynamic data updates from prior works.